2016
DOI: 10.1002/path.4739
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 deficiency in chondrocytes alleviates osteoarthritis development

Abstract: Activating transcription factor 3 (Atf3) has been implicated in the pathogenesis of various diseases, including cancer and inflammation, as well as in the regulation of cell proliferation and differentiation. However, the involvement of Atf3 in developmental skeletogenesis and joint disease has not been well studied to date. Here, we show that Atf3 is a critical mediator of osteoarthritis (OA) development through its expression in chondrocytes. ATF3 expression was markedly up-regulated in the OA cartilage of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…chondrocytes (48) and that the NF-kB signaling pathway triggers production of catabolic and inflammatory biomarkers in chondrocytes (49). In the current study, the results suggest that ghrelin activated Akt signaling and promoted anabolism of chondrocytes while suppressing the expression of catabolic and inflammatory biomarkers.…”
Section: Ghrelin Antagonizes Exaggerated Catabolism In Degenerative Csupporting
confidence: 55%
See 1 more Smart Citation
“…chondrocytes (48) and that the NF-kB signaling pathway triggers production of catabolic and inflammatory biomarkers in chondrocytes (49). In the current study, the results suggest that ghrelin activated Akt signaling and promoted anabolism of chondrocytes while suppressing the expression of catabolic and inflammatory biomarkers.…”
Section: Ghrelin Antagonizes Exaggerated Catabolism In Degenerative Csupporting
confidence: 55%
“…Disorganization of metabolism in OA involves impaired anabolism and abnormally enhanced catabolism, and activation of NF‐κB signaling is known to play a predominant role in cartilage degradation of OA (47). It is reported that NF‐κB signaling represses anabolism of chondrocytes (48) and that the NF‐κB signaling pathway triggers production of catabolic and inflammatory biomarkers in chondrocytes (49). In the current study, the results suggest that ghrelin activated Akt signaling and promoted anabolism of chondrocytes while suppressing the expression of catabolic and inflammatory biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Embryos were then immersed in Alcian blue solution overnight, and were transferred in a solution of 2% KOH, followed by staining in alizarin red solution overnight. Finally, the skeletons were cleaned with 1% KOH/20% glycerol and then stored in 50% ethanol/50% glycerol (Iezaki et al., 2016). …”
Section: Methodsmentioning
confidence: 99%
“…First shown to promote collagen synthesis and cell type-specific genes in OBs, it was subsequently found to stimulate CC proliferation and PHC differentiation, namely through upregulating Ihh expression [147]. Although earlier studies suggested that ATF3 could participate in promoting HC differentiation, conditional inactivation in chondrocytes ( Col2Cre ), revealed that ATF3 is dispensable for cartilage development [148]. The factor, however, exacerbates post-traumatic osteoarthritis downstream of inflammatory cytokines.…”
Section: Basic-domain Transcription Factorsmentioning
confidence: 99%